Implementasi Model Pembelajaran Kooperatif Learning Tipe Make A Match Dalam Pembelajaran PAI dan Budi Pekerti Untuk Meningkatkan Rasa Percaya Diri Siswa - Rido, Muhammad Ali; Muliati, Indah (Prodi Pendidikan Keagamaan Islam, 2025)
The background to this research is that during the PAI and Moral Education learning process, many students show low self-confidence, which is reflected in the lack of active participation in group discussions and difficulties in expressing opinions in class. The aim of this research is to find out how to implement the Make A Match type cooperative learning model in Islamic Education and Character learning and its effect on increasing the self-confidence of class VIII students at SMP N 43 Padang. This research uses descriptive qualitative methods. The research results show that this model has been implemented well, starting from the planning stage carried out by the teacher through the preparation of teaching modules and careful planning of learning implementation. Furthermore, the implementation of learning by Islamic Religious Education (PAI) teachers has proceeded according to the established model steps. At the evaluation stage, teachers use formative and summative evaluation. All these stages create a fun and interactive learning atmosphere, so that it can increase students' self-confidence.